2003
DOI: 10.1056/nejmoa022289
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microsatellite-Instability Status as a Predictor of Benefit from Fluorouracil-Based Adjuvant Chemotherapy for Colon Cancer

Abstract: BACKGROUND-Colon cancers with high-frequency microsatellite instability have clinical and pathological features that distinguish them from microsatellite-stable tumors. We investigated the usefulness of microsatellite-instability status as a predictor of the benefit of adjuvant chemotherapy with fluorouracil in stage II and stage III colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

55
1,339
11
50

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,969 publications
(1,455 citation statements)
references
References 45 publications
55
1,339
11
50
Order By: Relevance
“…The relationship between TANs and chemotherapy efficacy needs further study. Although the use of MMR status to predict the outcomes of adjuvant chemotherapy is still controversial, the results from previous trials are very promising and indicate that 5‐FU is beneficial for treating dMMR CRC 28, 32, 33. A large multicenter AGEO study indicated that high‐risk stage II dMMR colon cancer tended to have better outcomes with oxaliplatin‐based adjuvant chemotherapy than with surgery alone 34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between TANs and chemotherapy efficacy needs further study. Although the use of MMR status to predict the outcomes of adjuvant chemotherapy is still controversial, the results from previous trials are very promising and indicate that 5‐FU is beneficial for treating dMMR CRC 28, 32, 33. A large multicenter AGEO study indicated that high‐risk stage II dMMR colon cancer tended to have better outcomes with oxaliplatin‐based adjuvant chemotherapy than with surgery alone 34.…”
Section: Discussionmentioning
confidence: 99%
“…dMMR CRCs are notable for greater survivability, particularly in Stage II/III CRC 28, 30, 31. Retrospective studies have demonstrated improved survival in patients with MMR‐competent tumors after receiving 5‐FU‐based chemotherapy 32, 33. A large multicenter study supports the use of adjuvant chemotherapy with fluoropyrimidine plus oxaliplatin for stage III‐dMMR colon cancer 34.…”
Section: Introductionmentioning
confidence: 99%
“…3. Chemotherapy response -Although with conflicting results, a large amount of preclinical and clinical evidence suggests a possible reduced response to 5-FU based chemotherapy in dMMR tumours (Benatti et al, 2005;Hutchins et al, 2011;Ribic et al, 2003;Sargent et al, 2010) According to the National Comprehensive Cancer Network (NCCN), MMR testing should be considered for all patients with stage-II disease, as stage-II MSI tumours have a good prognosis and may not benefit from chemotherapy (NCCN, 2015). 4.…”
Section: Introductionmentioning
confidence: 99%
“…MSI has been reported by several studies to be a marker of good prognosis in CRC and a meta-analysis of 2,935 stage II or III CRCs found better overall survival for MSI or defective DNA mismatch repair (hazard ratio (HR) = 0.67, 95 % CI 0.58 -0.78) ( 8 ). In addition, it has been suggested that MSI predicts absence of benefi t from 5-fl uorouracil--based adjuvant chemotherapy ( 9,10 ).…”
Section: Introductionmentioning
confidence: 99%